Cognitive decline on the Repeatable Battery for the Assessment of Neuropsychological Status in progressive supranuclear palsy. Issue 3 (2nd April 2020) - Duff, Kevin; Randolph, Christopher; Boxer, Adam L.
Abstract: Objective: Progressive supranuclear palsy (PSP) is associated with a variety of cognitive deficits, but few studies have reported on its cognitive trajectory across time, especially on the Repeatable Battery for the Assessment of Neuropsychological Status (RBANS). Methods: Two hundred twenty participants diagnosed with Richardson's syndrome of PSP (PSP-RS) were evaluated with the RBANS at baseline, six months, and one year with alternate forms. Results: When using dependent t -tests, significant declines were observed on all Indexes of the RBANS from baseline to six months (ps < 0.01). Between six months and one year, significant declines were observed on three Indexes of the RBANS (ps < 0.05). Using existing regression-based change formulae from cognitively intact older adults, these participants with PSP showed significant decline on all RBANS Indexes (ps < 0.01) across one year. Finally, new regression-based change formulae were developed on this sample of individuals with PSP-RS to more precisely evaluate cognitive change in this condition. Conclusion: In this large, longitudinal cohort of participants with PSP-RS, many (but not all) showed notable cognitive decline across six months and one year on the RBANS. The different methods of examining change across time yielded different results, with regression-based methods appearing to more accurately capture decline in this sample. These findings are expected to allow clinicians to more accurately evaluate cognitive trajectories in patients with PSP, as well as make better estimates of prognosis and offer more appropriate treatment recommendations. Such findings are also expected to inform clinical trials as to the changes in cognitive outcomes with this neurological condition.